Analysis of sweet corn growth and yield with the use of organic cow manure fertilizer - Nurmalasari, Aprilia Ike; Supriyono, Supriyono; Linda, Franciska; Sukaya, Sukaya (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2024)
Sweet corn is a horticultural crop that is widely cultivated and consumed by Indonesian people. Meeting the demand for sweet corn is still reliant on imports; therefore, increasing production by improving soil properties through proper fertilization. Cow manure with a content of N 2.33%, P 0.61%, and K 1.58% is able to add nutrients to the soil. This research aimed to obtain an optimum dose of organic fertilizer for sweet corn growth and yield. The doses of cow manure consisting of 5 levels: control, 10, 20, 30, and 40 tons ha⁻¹ were assigned in the randomized complete block design with 5 replications. Data analysis deployed analysis of variance (Anova) at 5% level, and if there were significant differences, it would be proceeded to Duncan Multiple Range Test 5% and orthogonal polynomial. The results showed that a dose of 20 tons ha⁻¹ was able to increase growth in plant height, stem diameter and number of leaves by 12.92%, 26.29%, and 15.67%, respectively, compared to the control. A dose of 35 tons ha⁻¹ can produce a weight of cob-husk and cob without-husk per plot, respectively, 4.38 kg plot⁻¹ and 2.64 kg plot⁻¹, and a productivity of cob-husk of 5.30 tons ha⁻¹. A dose of 38 tons ha⁻¹ can produce a cob without-husk productivity of 3.29 tons ha⁻¹.